Greening China The Benefits of Trade and Foreign Direct Investment - Eastin, Joshua (University of Michigan Press, 2011)
China has earned a reputation for lax environmental standards that allegedly attract corporations more interested in profit than in moral responsibility and, consequently, further negate incentives to raise environmental standards. Surprisingly, Ka Zeng and Joshua Eastin find that international economic integration with nation-states that have stringent environmental regulations facilitates the diffusion of corporate environmental norms and standards to Chinese provinces. At the same time, concerns about â€œgreenâ€_x009d_ tariffs imposed by importing countries encourage Chinese export-oriented firms to ratchet up their own environmental standards. The authors present systematic quantitative and qualitative analyses and data that not only demonstrate the ways in which external market pressure influences domestic environmental policy but also lend credence to arguments for the ameliorative effect of trade and foreign direct investment on the global environment.